Community health workers' experiences in the care of clients with chronic illness in Julesburg, greater Tzaneen Municipality, South Africa - Mashele, Tintswalo Johanna (My University, 2021)
Background: Chronic illnesses, including non-communicable diseases (NCDs), continue to be a public health concern, globally, and contribute to the high burden of diseases. These health challenges have led to the introduction of community health workers (CHWs) in both developed and developing countries as a way of dealing with these challenges. It is more than five years since ward-based outreach teams (WBOTs) were introduced into the Julesburg area in order to respond to the needs of the community, based on the government’s focus on quadruple burden of diseases. The researcher is aware of the increasing workload, unclear roles and responsibilities, different approaches to CHWs’ work taken, and the ever-changing focus of their work, based on the community needs and diseases that the community faces at a particular time. It is for this reason that the researcher is interested in understanding the CHWs’ experiences and the manner in which they cope with challenges when working in their ever-changing environment, workload, work focus and roles and responsibilities. Methods: A qualitative exploratory, descriptive and contextual study approach was used; data was collected using focus group discussions with CHWs and one-on-one interviews with key informants, using their supervisors to gather more information that could not have been shared by CHWs. Result: The findings from the focus group discussions revealed that the CHWs have a high workload, while receiving stipend and are not permanently employed. CHWs have had experiences that make them feel unimportant and not needed, as well as enduring poor working conditions without sufficient personal protective equipment (PPE). Even though they experience dissatisfaction, they are passionate about continuing with their community-based work for many years, evidenced by those who have up to 22 years of service.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Community Health Worker; Experiences; Healthcare; Chronic illnesses; Non-Communicable Diseases; Ward-Based Outreach Team; Community health services; Community health aides; Medical personnel; Chronic diseases